PEMIKIRAN POLITIK ABDURRAHMAN WAHID TENTANG DEMOKRASI DI INDONESIA - Abdul Muchit Fajar; Hotrun Siregar, MSi. (Universitas Bung Karno, 2021)
AbstractThis research wants to know how democracy should be applied together with the Indigenousization of Islam in Abdurrahman Wahid's view. From this research, it is known that the constitutionalization of democracy through efforts to realize the rule of law is the main prerequisite for democracy. The Pancasila democracy that was initiated by the New Order was simply described by Abdurrahman Wahid as a